Financial Control and Financial Monitoring within the System of Government Financial Administration: Correlations and Interrelationships - VLASOVA, Elena Lvovna; BARASHEVA, Elena Victorovna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).37, 2018)
This paper describes some of the terminology related to financial control, financial oversight, and financial monitoring, examines the correlation among them, and looks into the essence of and the interrelationship among these fundamental elements of financial administration. The relevance of the issue of enhancing the system of government financial control using financial monitoring and boosting its efficiency, its undoubted theoretical and practical significance, and the insufficient amount of research into it may be prompting researchers in the area of government financial administration to undertake a set of objectives resolving which should help improve the nation’s system of financial administration significantly. In contrast with financial control and financial oversight, scholarly/ theoretical research devoted to organizing and implementing financial monitoring in keeping with present-day requirements and taking account of the development of market relations is merely in its incipience at this time. The purpose of the research reported in this paper is to analyze the correlation among financial control, financial oversight, and financial monitoring as inseparably interrelated elements, as well as explore the characteristics of the distribution of functions on their implementation across the nation’s entities concerned with government financial administration. The authors provide an insight into Russia’s current statutory/ legal and organizational support for financial monitoring, its system of authorities concerned with regulating the nation’s financial sphere, and the characteristics of the organization of the system of government financial monitoring in foreign countries. Based on the findings from this study, the authors propose putting in place a single information base for the purposes of implementing government financial control and explore the prospects for interaction between institutions and the authorities concerned with administering government financial control. The authors conclude that at this time there, without question, are certain areas within the existing system of government financial control that need substantial work.